Study of Optical, Physical and Upconversion Properties of Tellurite Base Glasses Codoped With Lanthanide Ions-A Review: Exploring the Potential of Tellurite Base Glasses Codoped With Lanthanide Ions (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Tellurite base glasses are highly promising candidate in the field of photonics. Since last three decades researchers are working on tellurite base glasses doped with heavy metal oxides(HMOs) and codoped with lanthanide ions. HMO moderate the physical properties where as lanthanide ions are used to activate upconversion properties.